THE EFFECT OF ADDING SPECIFIC HIP STRENGTHENING EXERCISES TO CONVENTIONAL KNEE EXERCISES IN PATIENTS WITH PATELLO FEMORAL PAIN SYNDROME (International Journal of Physiotherapy, 2016)
Background: Patello femoral pain Syndrome is an over use injury and one of the commonest problems seen in adolescents who are physically active. Till date no study has been done comparing the effect of adding specific hip strengthening exercises (gluteus medius, gluteus maximus & lateral rotators) to conventional exercises in patients with Patello femoral Pain Syndrome (PFPS) while minimizing the effect of minimizing the activation of tensor fascia lata (TFL).Methods: 30 subjects were randomly allocated using convenience random sampling into 2 Groups Group A and Group B with 15 subjects in each group. Readings were taken for Numeric Pain Rating Scale (NPRS), Manual Muscle Testing (MMT) for hip abductors, extensors and external rotators muscles quadriceps and hamstrings, and Anterior Knee Pain Scale (AKPS) on baseline and at the end of 4th week.Results: Analysis of the data collected for NPRS, AKPS and MMT of Quadriceps, Hamstrings, Hip Abductors and Hip External Rotators of 30 subjects was done by statistical analysis tests using STATA and software version 11.2. Although improvement was seen in both the groups but group B improved better compared to group A.Conclusion: Group B treatment protocol i.e. Hip specific strengthening (gluteus medius and gluteus maximus) in addition to conventional treatment in patients with patello-femoral pain syndrome, was found to be effective in reducing pain, improving functional status and increasing muscle strength than Group A treatment protocol i.e. Knee strengthening and stretching.